Adaptive game-based learning in education: a systematic review - Chiotaki, Domna; Poulopoulos, Vassilis; Karpouzis, Kostas (Frontiers in Computer Science, 2023)
The advent and abundance of mobile devices and network connectivity have provided learners of all ages with access to potentially unlimited sources of educational material, from pre-school activities to conventional and after-school courses and continuing education. One of the challenges that learners face is how to locate and access interesting content, suited to their preferences and, more importantly, level of expertise and individual needs. From the point of view of content creators and educators, adapting the content and the experience to each learner usually leads to better user retention and a more meaningful and deeper learning experience. In this paper, we utilize the PRISMA review methodology to examine research on content and experience adaptivity in educational contexts and report on the authors' findings. Consisting of well-defined steps (keyword-based retrieval, study scope definition, result filtering, and grouping and analysis), the systematic nature of this methodology ensures its objectivity and replicability at a future stage or replicated by other researchers.